The Implementation of Merdeka Curriculum in Piloting Madrasa; A Case Study at State Madrasah Ibtidaiyah of Semarang City - Ali Imron (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis research examines the implementation of the Merdeka Curriculum at State Madrasah Ibtidaiyah (MIN) of Semarang City, Central Java, Indonesia. This type of research is qualitative research with a descriptive-analytical approach. The Data of this study are collected through interviews and documentation, while the analysis technique used is the Miles and Huberman model, including data reduction, data presentation, and conclusions. The results showed that the implementation of the Merdeka Curriculum at MIN of Semarang City has been effective despite facing obstacles. Some obstacles are a lack of experience in implementing the Merdeka Belajar approach, the references and access to learning resources, the facilities and the amenities, and the understanding of scoring and assessment. However, these obstacles can be overcome with several supporting actors, including the active participation of teachers and madrasahs, the use of Merdeka Belajar platforms, the continuity of evaluation and improvement, and assistance from supervisors. The impact of implementation, including the changes in learning methods, innovation, the development of student independence, increased creativity and initiative, the relevance of learning, and increased student collaboration, bring positive impacts in improving the quality of learning and the outcomes of the student.Keywords: implementation of merdeka curriculum, madrasa piloting, continuous improvement.AbstrakPenelitian ini mengkaji tentang implementasi kurikulum merdeka di MIN of Semarang City, Jawa Tengah, Indonesia. Jenis penelitian ini merupakan penelitian kualitatif sehingga pendekatan yang digunakan dalam penelitian ini ialah pendekatan deskriptif-analitis.. teknik pengumpulan data pada penelitian ini melalui wawancara dan dokumentasi, sedangkan teknik analisisnya menggunakanmodel Miles dan Huberman yang mencakup tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi Kurikulum Merdeka di MIN of Semarang City telah berjalan efektif, meskipun menghadapi kendala seperti kurangnya pengalaman dalam menerapkan pendekatan merdeka belajar, keterbatasan referensi dan akses ke sumber belajar, keterbatasan sarana dan fasilitas, dan keterbatasan pemahaman dalam penilaian dan asesmen. Akan tetapi hambatan tersebut dapat diatasi dengan beberapa faktor pendukung yang meliputi partisipasi aktif guru dan madrasah, pemanfaatan platform merdeka belajar, evaluasi dan perbaikan terus-menerus, dan pendampingan dari pengawas. Dampak implementasi termasuk perubahan metode pembelajaran, inovasi, pengembangan kemandirian siswa, peningkatan kreativitas dan inisiatif, relevansi pembelajaran, dan peningkatan kolaborasi siswa, membawa dampak positif dalam meningkatkan kualitas pembelajaran dan hasil belajar siswa secara keseluruhan.Kata kunci: Implementasi kurikulum merdeka; Madrasah percontohan; perbaikan berkelanjutan.